Population structure of Haemonchus contortus from seven geographical regions in China, determined on the basis of microsatellite markers. Issue 1 (December 2016) - Yin, Fangyuan; Gasser, Robin; Li, Facai; Bao, Min; Huang, Weiyi; Zou, Fengcai; Zhao, Guanghui; Wang, Chunren; Yang, Xin; Zhou, Yanqin; Zhao, Junlong; Fang, Rui; et al.
Abstract Background Studying genetic variation within and amongHaemonchus contortus populations can inform some aspects of this parasite's population genetics and epidemiology. However, almost nothing is known about such variation in China. Methods Adult males ofH. contortus (n  = 184) representing seven distinct populations in China were collected, and genetic variation within and among these populations was explored using eight distinct microsatellite markers. Results Genetic parameters, such as heterozygosity and inbreeding coefficient (F IS ) indicated that all eight microsatellites were highly polymorphic. Various analyses (AMOVA, F ST, phylogenetic, structure, mantel test and population dynamics) revealed high within-population variation, low population genetic differentiation and high gene flow forH. contortus in China. Conclusions This study provides a first snapshot of the genetic substructuring ofH. contortus populations in China using polymorphic markers, and might provide a starting point for assessing genetic changes over space and time during or following the implementation of particular treatment or control strategies, or changes as a consequence of environmental, management and climatic factors.